AGROINDUSTRI SAYURAN SEBAGAI MODEL TANGGUH COVID-19 - Nunuk Hariyani; Muh. Agus Ferdian (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The impact of covid-19 pandemic, has become a complex and actual phenomenon, particularly for Indonesian people and more than 200 affected countries. Currently, 22 countries have experienced economic recession. Planting vegetables with hydroponic and organic systems is still considered difficult and not widely known by many people. Parents of the students and the surrounding community helped grow vegetables in the Pesantren (Islamic boarding school) and in their homes after participating the training and vegetable crop grants, in PPTQ Nuurun ala Nuur. Therefore, it is necessary to conduct research on the level of community participation, thus their participation can be increased to become a resilient village, towards a city and Indonesian nation that is resilient to the impact of COVID-19 pandemic. The purpose of this study is to describe, analyze and interpret; (1) the form of community participation (2) the degree of community participation, and (3) the typology of community participation in planting vegetables in Islamic boarding school and in their respective homes. This study used a qualitative approach, collecting data with interview techniques, questionnaires, observation and documentation. Data analysis used interactive techniques from Milis and Huberman. The validity of research data used trustworthiness, transferability, dependence and certainty. The results of this study include: (1) The process of community group discussions, (2) Community empowerment, (3) Utilization of community outcomes in health, economy and environment towards a COVID-resilient society, (4) The degree of spontaneous participation, (5) The degree of induced participation, (6) The degree of depressed participation, (7) The degree of economic participation (8) The role of intensive participation, (9) The role of functional participation and (10) The role of community participation independently